Factores psicosociales que intervienen en el rendimieto académico de los estudiantes de la Carrera de Cultura Física y Entrenamiento Deportivo, de la Universidad Nacional de Chimborazo, durante el período académico septiembre 2014- febrero 2015. - Rodríguez Sotomayor, César Mario (2016)
The objective of this research was to analyze the psychosocial factors involved in academic performance of students in the career of Physical Culture and Sports Training of the National University of Chimborazo, in the academic period September 2014 - February 2015, the study sample it was 72 students, a population of 97 students, 57 male and 15 female, between a quantitative methodology used qualitative and, bibliographic and experimental quasi-transverse field research was applied; for data collection instruments used were academic record and a questionnaire that served to identify psychosocial factors of students was developed. Among the most relevant results it evidenced that corresponding to 100% of 97 students, only 25, ie 25.77% exceeded the required score to pass the semester, so 72 students representing 74.22% who obtained a score less than that required for approval. Among the psychosocial factors influencing academic performance of the students they were always cigarette consumption was 25%, while 55.56% had difficulty sometimes properly distribute their time to educational tasks. Program of Psychology Intervention was implemented through different thematic workshops to improve the academic performance of students.